Supramolecular Complexes in Cell Death and Inflammation and Their Regulation by Autophagy - Gentle, Ian E. (Frontiers in Cell and Developmental Biology, 2019)
Signalling activation is a tightly regulated process involving myriad posttranslational modifications such as phosphorylation/dephosphorylation, ubiquitylation/deubiquitylation, proteolytical cleavage events as well as translocation of proteins to new compartments within the cell. In addition to each of these events potentially regulating individual proteins, the assembly of very large supramolecular complexes has emerged as a common theme in signal transduction and is now known to regulate many signalling events. This is particularly evident in pathways regulating both inflammation and cell death/survival. Regulation of the assembly and silencing of these complexes plays important roles in immune signalling and inflammation and the fate of cells to either die or survive. Here we will give a summary of some of the better studied supramolecular complexes involved in inflammation and cell death, particularly with a focus on diseases caused by their autoactivation and the role autophagy either plays or may be playing in their regulation.